Dynamic Modelling for Reliability Analysis of Power Supply Systems in a Large European Hospital by Petri Nets, Fuzzy Inference System, Stochastic or Markov Chains - Pinto, Constâncio António (2022)
Tese de Doutoramento em Engenharia Mecânica, Sistemas Avançados de Produção, apresentada à Faculdade de Ciências e Tecnologia da Universidade de Coimbra.